Pagsasaespasyo at Pagpopook sa mga Pagkaing Pilipino sa New South Wales, Australia (The Spatialization and Localization of Filipino Foods in New South Wales, Australia) - Tugano, Axle Christien (Social Sciences and Development Review, 2023)
The main objective of this study is to trace the roots of the relationship between the Philippines and Australia—one that goes beyond the conventional frameworks focused mainly on diplomacy, politics, and other state-to-state or nation-to-nation concerns—frameworks that often leave behind and fail to give adequate voice and attention to the significance of the people as a whole. The dominance of Western perspectives in Area Studies and Regionalism Studies has constrained the emergence of a distinctly Filipino-Asian identity. Therefore, to elevate and center the people, this study adopts a perspective grounded in the framework of Araling Kabanwahan and Kasaysayang Kabanwahan to examine the connections or linkages between the Philippines and lands overseas. In this case, the research focuses on the spatialization and localization of Filipino foods in New South Wales, Australia, as a way to represent and perform the “Filipino nation” on the stage of a “foreign land.” Likewise, this study contributes to the ongoing enrichment of the concept of Kalutong Bayan (People’s Cuisine or National Cuisine). Apart from the researcher’s direct participation in the Australian context, the study also employs indigenous Filipino research methods—such as pagtatanong-tanong (informal interviewing), pakikipagkuwentuhan or pagpapakuwento (story sharing), patikim-tikim (tasting), pagtingin-tingin (observing), and pagsusuruy-suroy (wandering or immersing)—which have long been cultivated in the field of Filipinization.